2013
DOI: 10.1101/gad.221648.113
|View full text |Cite
|
Sign up to set email alerts
|

Subnuclear partitioning of rRNA genes between the nucleolus and nucleoplasm reflects alternative epiallelic states

Abstract: Eukaryotes can have thousands of 45S ribosomal RNA (rRNA) genes, many of which are silenced during development. Using fluorescence-activated sorting techniques, we show that active rRNA genes in Arabidopsis thaliana are present within sorted nucleoli, whereas silenced rRNA genes are excluded. DNA methyltransferase (met1), histone deacetylase (hda6), or chromatin assembly (caf1) mutants that disrupt silencing abrogate this nucleoplasmic-nucleolar partitioning. Bisulfite sequencing data indicate that active nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
176
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(181 citation statements)
references
References 28 publications
3
176
0
2
Order By: Relevance
“…There was extensive demethylation of some rRNA genes, particularly in root tissue, involving the Pol I promoter region in 3 (8%) P-genome and 1 (100%) D-genome genes. Given that transcriptionally active rDNA units are extensively demethylated in Arabidopsis (Pontvianne et al, 2013), we suggest that about 10% of P-genome rRNA genes become activated in plant 33A. Thus, there are about 130 active rDNA genes, corresponding to 70 D-genome rRNA genes and 60 P-genome rRNA genes.…”
Section: Discussionmentioning
confidence: 99%
“…There was extensive demethylation of some rRNA genes, particularly in root tissue, involving the Pol I promoter region in 3 (8%) P-genome and 1 (100%) D-genome genes. Given that transcriptionally active rDNA units are extensively demethylated in Arabidopsis (Pontvianne et al, 2013), we suggest that about 10% of P-genome rRNA genes become activated in plant 33A. Thus, there are about 130 active rDNA genes, corresponding to 70 D-genome rRNA genes and 60 P-genome rRNA genes.…”
Section: Discussionmentioning
confidence: 99%
“…In somatic leaf nuclei, condensed silent heterochromatic portions of rDNA loci coincide with chromocenters that contain centromeric heterochromatin at the external periphery of the nucleolus, a subnuclear compartment where rDNA transcription and ribosome assembly take place, and only relatively few rRNA genes are located within the nucleolus to be transcribed (22). Distinct megabase-sized clusters of rRNA gene variant repeats are selectively silenced during early embryonic development; are excluded from the nucleolus; and are not transcribed in somatic tissues, including leaves (23,24).…”
Section: Cdc48a-mediated Centromeric Heterochromatin Decondensationmentioning
confidence: 99%
“…Distinct sequence variants of the 45S rRNA genes exist, which have either extra-or intra-nucleolar localization. 30 This homeostasis is compromised in the CAF-1 mutants fasciata, where rDNA copies are progressively lost and the originally inactive rRNA gene copies translocate into the nucleolus and are expressed. 30,31 Jiri Fajkus (Brno, Czech Republic) showed that the reintroduction of a wild-type FAS allele into fas mutant plants that have been inbred for several generations can lead to reversion of the rRNA gene copy-number but causes major changes in the bulk variant composition, their transcriptional state and nuclear localization, suggesting reprogramming and establishment of a novel epigenetic equilibrium at the nucleolus organizer regions in these plants.…”
Section: Organized Genome In An Organized Nucleusmentioning
confidence: 99%
“…32 A potential role of the nucleolus as a compartment sequestering transcriptionally repressed parts of genome away from the RNAP II territory was presented by Frederic Pontvianne (Perpignan, France). Fluorescence-assisted sorting of nucleoli 30 followed by DNA sequencing revealed that, in addition to rRNA genes, also RNAP II-transcribed genomic DNA sequences can localize within the nucleolus, defining nucleolus-associated domains (NADs) in plants (Fig. 3).…”
Section: Organized Genome In An Organized Nucleusmentioning
confidence: 99%
See 1 more Smart Citation